Counteracting student resistance to spaced learning using the Theory Of Planned Behavior - Mattingly, Victoria Prescott, author; Kraiger, Kurt, advisor; Rhodes, Matthew, committee member; Beier, Margaret, committee member; Chermack, Thomas, committee member (Colorado State University. Libraries, 2015)
Despite the proven benefits of spaced learning, students are reluctant to use this study technique. I proposed that students do not space their studying because they lack basic competencies needed to successfully engage in this behavior. According to the Theory of Planned Behavior, behaviors are the product of one’s intentions, which are derived from attitudes and beliefs. Using this theoretical framework, I designed and evaluated a classroom intervention with the goal of changing debilitating attitudes towards spaced learning. I hypothesized that students exposed to this spaced learning classroom intervention would have stronger intentions to space, higher rates of spaced learning behaviors, and consequently higher exam scores compared to the control group. Intentions to space and the beliefs and attitudes contributing to those intentions were improved by the classroom intervention. Students who spaced their studying also performed better on the exam compared to students who did not space. However, the classroom intervention did not significantly predict whether or not students would space their studying. Implications and future research directions based on the study's findings are also discussed.
Keywords: distributed practice; spaced learning; spacing effect; theory of planned behavior